Investigation of Macular Choroidal Thickness and Blood Flow Change by Optical Coherence Tomography Angiography After Posterior Scleral Reinforcement - Zhang, Zheng; Qi, Yue; Wei, Wenbin; Jin, Zi-Bing; Wang, Wen; Duan, Anli; Liu, Wu (Frontiers in Medicine, 2021)
PURPOSE. To study the effect of posterior scleral reinforcement (PSR) on choroidal thickness (CT) and blood flow. METHODS. This study included 25 eyes of 24 patients with high myopia (≤ -6.0 dioptres or axial length ≥ 26.0 mm) which underwent PSR surgery. All patients completed the 1-month follow-up visit. Myopic macular degeneration (MMD) was graded according to the International Meta-Analysis for Pathologic Myopia (META-PM) classification based on color fundus photographs. Swept-source optical coherence tomography angiography (SSOCTA) was performed to investigate CT, choroid perfusion area (CPA) and choriocapillaris perfusion area (CCPA) change following PSR surgery. RESULTS. The distribution of MMD categories was 9 (36.0%) in category 1, 10 (40.0%) in category 2, 6 (24.0%) in category 3 or category 4. MMD severity was strongly correlated with CT (all P < 0.01) and CPA (all P < 0.04). Postoperative CT at each sector increased significantly at 1 week’s follow-up, compared to pre-operative measure (all P < 0.05). Postoperative CPA at subfoveal, superior, inferior, and nasal sectors also increased significantly 1-week after PSR surgery (all P < 0.05). Moreover, the increased CT, CPA and CCPA remain after PSR surgery at 1 month’s follow-up, but the difference was not statistically significant. CONCLUSIONS. We demonstrated that the choroidal thickness and blood flow increased significantly in patients with high myopia who underwent PSR surgery in a short period of time. In addition, the CT and CPA were independently associated with MMD. However, whether the transient improvement of the choroid circulation could prevent long-term progression of high myopia warrant further study in the further.